2022
DOI: 10.1111/cdev.13828
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of moral disengagement and social norms as anti‐bullying components: A randomized controlled trial

Abstract: This three‐armed randomized controlled trial examined how moral disengagement and social norms account for change in bullying behavior and their potential as targets of anti‐bullying components within separate interventions among 1200 French‐speaking Belgian elementary students (48% boys, 9–12 year‐olds, 57 classes, nine schools) during 2018–2019 (no ethnicity data available). Mediation analysis revealed that students' moral disengagement successfully decreased (β = −.46), which, in turn, reduced both bullying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 75 publications
(113 reference statements)
0
18
0
Order By: Relevance
“…Specifically, class discussions and scenarios challenging moral disengagement justifications reduced moral disengagement levels and victimization (Wang & Goldberg, 2017). These findings have been extended to a randomized control trial by Tolmatcheff et al (2022) where it was found that moral disengagement decreased along with bullying and outsider behavior and defending increased. Encouraging similar adaptive coping strategies may therefore provide schools with constructive methods for minimizing adverse outcomes to bullying and intervene in the bullying cycle.…”
Section: Strengths and Limitationsmentioning
confidence: 74%
“…Specifically, class discussions and scenarios challenging moral disengagement justifications reduced moral disengagement levels and victimization (Wang & Goldberg, 2017). These findings have been extended to a randomized control trial by Tolmatcheff et al (2022) where it was found that moral disengagement decreased along with bullying and outsider behavior and defending increased. Encouraging similar adaptive coping strategies may therefore provide schools with constructive methods for minimizing adverse outcomes to bullying and intervene in the bullying cycle.…”
Section: Strengths and Limitationsmentioning
confidence: 74%
“…To decrease moral disengagement, teachers might consider using children's storybooks with bullying situations, and following them up with classroom discussion. By asking questions, teachers can help the students to be aware of, question, and reject each mechanism of moral disengagement in relation to aggression and bullying (Tolmatcheff et al, 2022;Wang & Goldberg, 2017). Students can also work with hypothetical stories in which they are asked to identify moral disengagement mechanisms, write individual reflections by identifying and describing recent cases in which they had done something they knew were wrong, describe their feelings and use of moral disengagement mechanisms, and then brainstorm in pairs or groups to identify alternatives they could have used instead of the moral disengagement mechanisms (Bustamante & Chaux, 2014).…”
Section: Implications For Practicementioning
confidence: 99%
“…These focus on individual-level factors (e.g., attitudes, beliefs, moral disengagement excuses), but they also focus on group- and classroom-level processes, such as the classroom climate, social norms, and the mobilization of peer bystanders (Jungert et al, 2016; Saarento et al, 2015; Salmivalli et al, 2005; Van Ryzin & Roseth, 2018). Second, the research designs of successful interventions are beginning to be informed by explanatory mechanisms and processes (hypothesized mediators) that reliably reduce victimization (Tolmatcheff et al, 2022). Here, we seek to open up the “black box” of successful antibullying programs (Saarento et al, 2015; Tolmatcheff et al, 2022).…”
Section: Role Of the Classroom Climate And Peer Bystanders In Deescal...mentioning
confidence: 99%
“…Here, we seek to open up the “black box” of successful antibullying programs (Saarento et al, 2015; Tolmatcheff et al, 2022). The present study represents a response to the field’s recent call to focus on explanatory mechanisms (Gaffney et al, 2021; Menesini & Salmivalli, 2017; Saarento et al, 2015; Tolmatcheff et al, 2022).…”
Section: Role Of the Classroom Climate And Peer Bystanders In Deescal...mentioning
confidence: 99%
See 1 more Smart Citation